Risk of birth defects by pregestational type 1 or type 2 diabetes: National Birth Defects Prevention Study, 1997–2011. Issue 1 (6th June 2022) - Marchincin, Stephanie L.; Howley, Meredith M.; Van Zutphen, Alissa R.; Fisher, Sarah C.; Nestoridi, Eirini; Tinker, Sarah C.; Browne, Marilyn L.
Abstract: Background: Previous studies found consistent associations between pregestational diabetes and birth defects. Given the different biological mechanisms for type 1 (PGD1) and type 2 (PGD2) diabetes, we used National Birth Defects Prevention Study (NBDPS) data to estimate associations by diabetes type. Methods: The NBDPS was a study of major birth defects that included pregnancies with estimated delivery dates from October 1997 to December 2011. We compared self‐reported PGD1 and PGD2 for 29, 024 birth defect cases and 10, 898 live‐born controls. For case groups with ≥5 exposed cases, we estimated adjusted odds ratios (aORs) and 95% confidence intervals (CIs) for the association between specific defects and each diabetes type. We calculated crude ORs (cORs) and 95% CIs with Firth's penalized likelihood for case groups with 3–4 exposed cases. Results: Overall, 252 (0.9%) cases and 24 (0.2%) control mothers reported PGD1, and 357 (1.2%) cases and 34 (0.3%) control mothers reported PGD2. PGD1 was associated with 22/26 defects examined and PGD2 was associated with 29/39 defects examined. Adjusted ORs ranged from 1.6 to 70.4 for PGD1 and from 1.6 to 59.9 for PGD2. We observed the strongest aORs for sacral agenesis (PGD1: 70.4, 32.3–147; PGD2: 59.9, 25.4–135). For both PGD1 and PGD2, we observed elevated aORs in every body system we evaluated, including central nervous system, orofacial, eye, genitourinary, gastrointestinal, musculoskeletal, and cardiac defects. Conclusions: We observed positive associations between both PGD1 and PGD2 and birth defects across multiple body systems. Future studies should focus on the role of glycemic control in birth defect risk to inform prevention efforts.